Service-Induced Campaign Contributions and the Electoral Equilibrium - Baron, David P. (Quarterly Journal of Economics, 1989)
Candidates for office are modeled as promising services, such as support for legislation and intervention in the bureaucracy, to interest groups in exchange for campaign contributions. An electoral equilibrium is characterized in which candidates choose service-contribution offers and interest groups choose whether to contribute. The model provides several explanations of congressional incumbents' success in over 90 percent of their reelection contests: a recognition advantage, a high personal valuation of the office, a lower cost of providing services, and policy alignment with high demand interest groups. The model yields predictions that are consistent with empirical findings on the relation between campaign contributions and election outcomes.